VIBRATION SENSORS AND MICROELECTROMECHANICAL SYSTEM FOR MOBILE DEVICES SUCH AS ANALOGS, FOR EVALUATION OF VIBRATION OF ROTARY MACHINES - B. A. Chichkov (Научный вестник МГТУ ГА, 2016)
The paper carried out a comparison of vibration sensors used to measure the vibration condition units with gas turbine engines, with motion sensors, microelectromechanical systems used in modern mobile devices (for example, devices on the platform "Android"). It provides opinions on the possibility of assessment of vibration, using sensors of mobile devices.